Relationship Between Sleep Quality and Quantity and Weight Loss in Women Participating in a Weight-Loss Intervention Trial - Thomson, Cynthia A. (Obesity (Silver Spring), 2012)
Evidence suggests that individuals who report fewer total hours of sleep are more likely to be overweight or obese. Few studies have prospectively evaluated weight-loss success in relation to reported sleep quality and quantity. This analysis sought to determine the association between sleep characteristics and weight loss in overweight or obese women enrolled in a randomized clinical trial of a weight-loss program. We hypothesized that in overweight/obese women, significant weight loss would be demonstrated more frequently in women who report a better Pittsburgh Sleep Quality Index (PSQI) Global Score or sleep >7 h/night as compared to women who report a worse PSQI score or sleep ≤7 h/night. Women of ages 45.5 ± 10.4 (mean ± SD) years and BMI of 33.9 ± 3.3 (n = 245) were randomized and completed PSQI at baseline and 6 months; 198 had weight change assessed through 24 months. At baseline, 52.7% reported PSQI scores above the clinical cutoff of 5. Better subjective sleep quality increased the likelihood of weight-loss success by 33% (relative risk (RR), 0.67; 95% confidence interval (CI), 0.52–0.86), as did sleeping >7 h/night. A worse Global Score at 6 months was associated with a 28% lower likelihood of continued successful weight loss at 18 months, but unassociated by 24 months. These results suggest that sleep quality and quantity may contribute to weight loss in intervention-based studies designed to promote weight control in overweight/obese adult women.